Analisis Syarat Pencalonan Anggota DPR dan DPRD yang Diatur oleh Peraturan KPU dan Undang-Undang Pemilu - I Gusti Ngurah Raka Wedatama; I Gusti Bagus Suryawan; I Wayan Arthanaya (Jurnal Analogi Hukum, 2019)
This thesis has a background through democracy that its implementation with elections held by the KPU with its authority at each stage of its election can form KPU regulations and stipulate KPU regulations Number 20 Year 2018 and in the process is considered to violate the higher regulations namely Number Election Law 7 of 2017 here regulates the prohibition of former corruption inmates to become candidates for DPR and DPRD members so that they can explain to the public the noble intentions of the institution towards the noble ideals of the nation about eradicating corruption. This has been a debate in the community, political elites and state institutions. What is the background of the formation of KPU regulations Number 20 Year 2018 and what are the implications of the Supreme Court's decision Number 46 P / HUM / 2018 this study is a normative legal research that is prescriptive and technical or applied. The research approach uses a legal approach and a case approach. The type of research data is secondary data with primary legal material and secondary legal material. Data collection techniques in the form of library studies and data analysis techniques used are deduction with syllogism methods. Through scrutiny of laws and regulations related to the Election Law No. 7 of 2017. After the research material was obtained and collected, the material can be concluded if the background and moral factors of the KPU form the KPU Regulation is in order to obey the noble ideals of the nation in eradicating corruption and giving the public legislative candidates with integrity and being able to carry out the decisions of the Supreme Court through forming KPU regulations No. 31 of 2018 as a substitute.